Collisions of three-component vector solitons in Bose-Einstein condensates - Lannig, Stefan; Schmied, Christian-Marcel; Prüfer, Maximilian; Kunkel, Philipp; Strohmaier, Robin; Strobel, Helmut; Gasenzer, Thomas; Kevrekidis, Panayotis G.; Oberthaler, Markus K. (Physical review letters, 2020)
Ultracold gases provide an unprecedented level of control for the investigation of soliton dynamics and collisions. We present a scheme for deterministically preparing pairs of three-component solitons in a Bose-Einstein condensate. Our method is based on local spin rotations which simultaneously imprint suitable phase and density distributions. This enables us to observe striking collisional properties of the vector degree of freedom which naturally arises for the coherent nature of the emerging multicomponent solitons. We find that the solitonic properties in the quasi-one-dimensional system are quantitatively described by the integrable repulsive three-component Manakov model.